ChemInform Abstract: Iridium‐Catalyzed Direct ortho‐C—H Amidation of Benzoic Acids with Sulfonylazides. Issue 17 (April 2016) - Wei, Ming‐E; Wang, Lian‐Hui; Li, Yu‐Dong; Cui, Xiu‐Ling
Abstract: affording various anthranilic acid derivatives